Enterprise Mac security : MAC OS X Snow Leopard - Edge, Charles S., Jr; Barker, William (Apress, 2010)
Contains detailed Mac OS X security information, and walkthroughs on securing systems, including the new Snow Leopard operating system. You'll learn the newest security techniques on Mac OS X, details of the new Mac OS X Snow Leopard Operating System for the desktop and server, and how to secure these systems, Mac forensics and Mac hacking, Apple wireless security, and more.